BAHASA POLITIK DALAM PERSPEKTIF FILSAFAT BAHASA LUDWIG WITTGENSTEIN - Wilujeng, Sri Rahayu (HUMANIKA, 2012)
ABSTRACT In Ancient Greek, human being is termed Homo ludens, a game-player animal. In Wittgenstein’s perspective, politics may then be defined as a game which needs a language game as a means of communication. All political systems practiced throughout the world use language games, and the democratic system is the one most dependent to its language game. Through the game, political institutions gain vote and collect sympathy from the people. By practicing language game one persuades others in order to have same opinion or idea. Therefore, one should be careful and critical in weighing political statements, questioning what meanings lie behind them, within the democratic system. Keywords: Wittgenstein, language game, democracy